Analisis Karakteristik Fisik Lahan Kawasan Perumahan di Dusun Jering VI, Desa Sidorejo, Kecamatan Godean, Kabupaten Sleman - Adifa, Fitri; Sungkowo, Andi (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
Land characteristics include land factors that can be measured or estimated in size such as slope, rainfall, soil texture, available water and so on. The study was conducted at a housing location in Jering VI Hamlet, Sidorejo Village, Godean District, Sleman Regency which is located on Mount Wungkal. The condition of Mount Wungkal before being used as housing had dense vegetation, but with the large-scale opening of housing land, there were changes that occurred on Mount Wungkal. The opening of the land caused several impacts on the environment so it is important to know the physical characteristics of the land in the area. Thus, the purpose of this study was to determine the physical characteristics of the land in the research area. The method used is the survey and mapping method in data collection and descriptive analysis. The results of the study obtained are the physical characteristics of the land of the Godean Jogja Hills housing area, there are several criteria that are appropriate and inappropriate. The criteria that are not appropriate are slope gradient, area of green open space, drainage infrastructure capacity, not located in a disaster-prone area (landslides, floods, erosion, and abrasion), not located in an agricultural/buffer cultivation area, distance to educational facilities, health facilities and trade and commerce facilities and the appropriate criteria are the area for building houses, water availability, not located in the border area of rivers/coasts/reservoirs/lakes/springs/irrigation channels/railways and safe flight areas, not located in protected areas, avoiding technical irrigation rice fields, wastewater disposal systems and garbage disposal systems